Organizing for multichannel sales and marketing - Carter, Bruce (Henry Stewart Talks, 2008)
What is the benefit?, Multichannel increases productivity through 'shift and lift', How can multichannel sales and marketing be used?, How did we segment the market?, How did we organize the desk based sales organization?, Key to integrate the channels with common systems and measures, Sample of coverage maps, Key metrics, Landscaping approach, Siebel based account development plan
Archived at 2022/03/17